The Determinants of Currency Hedging : Evidence from the Finnish Markets - Jutila, Arttu (My University, 2020)
The purpose of the thesis is to investigate the determinants of currency hedging in the Finnish markets. The sample consists of 106 non-financial firms listed on Nasdaq Helsinki in the year 2018. Logit regressions are estimated as the dependent variable is dichotomous. Different estimations are carried out to find the differences between currency hedgers and non-hedgers and to test robustness of the results. Five different models are estimated. Results imply that economies of scale, investment opportunity set, and foreign currency exposure are all important factors in hedging decision. Some evidence is provided for the relation between hedging and costs of financial distress, but the evidence is weak. Further, liquidity is an insignificant factor and leverage has some support behind it after excluding other hedgers from the non-hedging group. Currency hedgers are larger in terms of asset size and have higher foreign sales ratio. Hedgers spend more on research and development and distribute higher dividend yields than non-hedgers. Excluding other hedgers from the non-hedging sample results in stronger estimates. These results are robust through variety of tests with alterations on model specifications.
Keywords: derivatives; hedging; currency; currency risk; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance